Social Problems In The Novel Bumi Manusia By Pramoedya Ananta Toer (A Sociological Review Of Literature) - Ridwan Tawaqal; Nurhadi; Berliana Wahyu Ningtyas (Cita konsultindo, 2025)
The purpose of this study is to examine the social problems in Pramoedya Ananta Toer's novel